Pembuatan Bank TOGA sebagai Strategi Pelestarian Tanaman Obat Lokal di Nagari Labuh - Aulia Muslimah; Rayhan Abigail; Hammi Rogiba Lubis; Nur Alam; Siti Dwi Zahara; Armaita (FKIP - Universitas Pahlawan Tuanku Tambusai, 2024)
Family Medicinal Plants (TOGA) is an effort to use land for the cultivation of medicinal plants to meet the family's needs for natural medicines. Bank TOGA is the development of this concept, functioning as a center for conservation, education, and distribution of medicinal plants on a community scale. Nagari Labuh in Limo Kaum District, Tanah Datar Regency, has significant potential for the development of Bank TOGA due to the rich biodiversity of medicinal plants in this area. This study examines the implementation of Bank TOGA in Nagari Labuh as a strategy for the preservation of local medicinal plants. The program was carried out in five village's. The methods used include field surveys, coordination with related parties, and the implementation of participatory TOGA planting. The results showed the success of planting various types of medicinal plants and spices, the active participation of the community, and the potential for sustainability of the program. Challenges such as land limitations are overcome through innovative planting techniques. The implementation of Bank TOGA not only contributes to the preservation of medicinal plants, but also strengthens social cohesion, supports knowledge transfer between generations, and opens up new economic opportunities.